The Position of Religion In Development - Hijrin, Uus Husni; Kusnawan, Aep; Zuldin, Muhammad; Abidin, Yusuf Zainal; Wiwaha, Rizzaldy Satria (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study examines the position of religion in development through a descriptive-qualitative approach using literature review. Religion is not only understood as a spiritual belief system but also as a source of ethics, social guidance, and cultural power that shapes public policy and the direction of national development. In the Indonesian context, religion is closely linked to Pancasila and national identity, meaning that development is not entirely secular but grounded in divine values, social justice, and humanity. The findings indicate that religion contributes significantly to education, economy, socio-cultural life, politics, and environmental sustainability through institutions such as Islamic boarding schools (pesantren), zakat and waqf systems, religious philanthropy, interfaith moderation, and eco-theology. However, religion also faces challenges including secularization, politicization of faith, radicalism, commercialization of religion, and moral decline. Therefore, a constructive integration between religious values, scientific knowledge, and public policy is essential to achieve holistic, ethical, and sustainable development. Consequently, religion should not be seen as an obstacle to modernization but as a moral compass that guides development toward justice, dignity, and civility. Keywords: religion, development, ethics, Indonesia, religious moderation. AbstrakPenelitian ini membahas posisi agama dalam pembangunan dengan pendekatan kualitatif-deskriptif berbasis studi literatur. Agama dipahami bukan sekadar sistem kepercayaan spiritual, tetapi juga sebagai sumber etika, pedoman sosial, dan kekuatan budaya yang mempengaruhi kebijakan publik serta arah pembangunan nasional. Dalam konteks Indonesia, agama memiliki keterkaitan yang kuat dengan Pancasila dan identitas kebangsaan, sehingga pembangunan tidak bersifat sekuler murni, melainkan berlandaskan nilai Ketuhanan, keadilan sosial, dan kemanusiaan. Hasil pembahasan menunjukkan bahwa agama memiliki kontribusi signifikan pada bidang pendidikan, ekonomi, sosial-budaya, politik, dan lingkungan melalui pesantren, zakat-wakaf, filantropi, moderasi beragama, serta eco-theology. Namun, peran agama juga menghadapi tantangan seperti sekularisasi, politisasi agama, radikalisme, komersialisasi, dan degradasi moral. Oleh karena itu, diperlukan integrasi yang konstruktif antara nilai agama, ilmu pengetahuan, dan kebijakan publik agar pembangunan berjalan secara holistik, beretika, dan berkelanjutan. Dengan demikian, agama tidak menjadi hambatan modernisasi, tetapi berfungsi sebagai kompas moral (moral compass) dalam mewujudkan pembangunan yang adil, bermartabat, dan berkeadaban. Kata Kunci: agama, pembangunan, moral, Indonesia, moderasi beragama